An Analysis of the Eleventh-Grade Students’ Present Tense Errors in Writing Report Text - Nurfaida, Reza; Dwi Areni, Galuh Kirana (Universitas Pahlawan Tuanku Tambusai, 2025)
Mastering the simple present tense is crucial for writing factual texts like reports, yet many Indonesian EFL students struggle with it. This study identifies the types and causes of present tense errors in report texts written by seventeen eleventh-grade students at MAN 22 Jakarta. Using a qualitative descriptive method and Dulay, Burt, and Krashen’s Surface Strategy Taxonomy, the errors were classified as omission, addition, misformation, or misordering. A total of 187 errors were found, with misformation being the most common. The main causes were interlingual transfer, limited grammar knowledge, and direct translation from Bahasa Indonesia. Interviews confirmed that minimal practice and exposure also contribute to these errors. The findings underline the need for contextualized grammar instruction and engaging writing activities to help EFL students write more accurately and confidently.